Exploring the Factors Influencing School Students' Involvement in TVET: A Case Study in Kuala Rompin - WAN AHMAD RISAUDDIN, WAN NURFARIZA IZZATI; Mohd Zulfadli Rozali (Research and Innovation in Technical and Vocational Education and Training, 2025)
This study explores the underlying factors contributing to the limited involvement of secondary school students in Technical and Vocational Education and Training (TVET) in Kuala Rompin, Pahang. Despite various national policies and reforms aimed at promoting vocational education, participation rates among rural students remain low and inconsistent. Using a qualitative case study design, data were collected through semi-structured interviews with five key informants, including TVET lecturers, institutional administrators, and a district education officer. Thematic analysis, guided by Braun and Clarke’s (2006, 2021) framework, revealed five key themes: (1) social influence weakening student choices, (2) weak personal attraction toward TVET, (3) educational support gaps, (4) economic constraints and limited access to facilities, and (5) weak promotion and exposure to vocational pathways. These themes highlight how socio-cultural perceptions, institutional barriers, and economic limitations collectively shape students' disengagement from TVET. The findings offer insights into the complexity of educational inequalities in rural Malaysia and emphasize the need for policy reforms, improved institutional support, and stronger community-based promotion efforts to enhance TVET visibility and acceptance among school students. This study also contributes to theory by applying both Labeling Theory and Social Inequality Theory in the context of Malaysian vocational education.